Association of Serum Ferritin Levels Before Start of Conditioning With Mortality After alloSCT – A Prospective, Non-interventional Study of the EBMT Transplant Complications Working Party - Penack, Olaf; Peczynski, Christophe; van der Werf, Steffie; Finke, Jürgen; Ganser, Arnold; Schoemans, Helene; Pavlu, Jiri; Niittyvuopio, Riitta; Schroyens, Wilfried; Kaynar, Leylagül; Blau, Igor W.; van der Velden, Walter J. F. M.; et al. (Frontiers in Immunology, 2020)
Elevated serum ferritin levels occur due to iron overload or during inflammation and macrophage activation. A correlation of high serum ferritin levels with increased mortality after alloSCT has been suggested by several retrospective analyses as well as by two smaller prospective studies. This prospective multicentric study aimed to study the association of ferritin serum levels before start of conditioning with alloSCT outcome. Patients with acute leukaemia, lymphoma or MDS receiving a matched sibling alloSCT for the first time were considered for inclusion, regardless of conditioning. A comparison of outcomes between patients with high and low ferritin level was performed using univariate analysis and multivariate analysis using cause-specific Cox model. Twenty centres reported data on 298 alloSCT recipients. The ferritin cut off point was determined at 1500µg/l (median of measured ferritin levels). In alloSCT recipients with ferritin levels above cut off measured before the start of conditioning, overall survival (HR=2.5, CI=1.5-4.1, p=0.0005) and progression-free survival (HR=2.4, CI=1.6-3.8, p<0.0001) were inferior. Excess mortality in the high ferritin group was due to both higher relapse incidence (HR=2.2, CI=1.2-3.8, p=0.007) and increased non-relapse mortality (HR=3.1, CI=1.5-6.4, p=0.002). Non-relapse mortality was driven by significantly higher infection-related mortality in the high ferritin group (HR = 3.9, CI = 1.6-9.7 p = 0.003). Acute and chronic GVHD incidence or severity were not associated to serum ferritin levels. We conclude that ferritin levels before start of conditioning can serve as routine laboratory biomarker to predict mortality after alloSCT.